Opera omnia Desiderii Erasmi Roterodami Ordinis Sexti Tomus Tertius - Brown, Andrew J. (Huygens instituut/Brill, 2004)
This thirty-third volume in Erasmus' Opera omnia (ASD) is the third within 'ordo' VI, that is, the 'ordo' of the New Testament and the Annotations; the Paraphrases belong to 'ordo' VII. The division into 'ordines' - each 'ordo' being devoted to a specific literary or thematic category - was laid down by Erasmus himself for the posthumous publication of his works (see General introduction, ASD I, pp. x, xvii-xviii, and C. Reedijk, Tandem bona causa triumphat. Zur Geschichte des Gesamtwerkes des Erasmus von Rotterdam. Vortrage der AeneasSilvius- Stiftung an der Universitat Basel, XVI, Basel/Stuttgart, 1980, p. 12 sqq., 21-22). The present volume (tom. VI, 3, edited by Andrew J. Brown, London) contains the third part of Erasmus' edition of the Nouum Testamentum (Greek and Latin text), to wit RomanS-2 Thessalonians. The other books of the Nouum Testamentum will be published in ASD VI, 1 and VI, 4. Tom. VI, 2 (John and Acts, ed. Andrew J. Brown) was published in 2001. ASD VI, 5-10 will comprise the Annotations on the New Testament, of which already have been published: tom. VI, 5 (Annot. on Matthew-Luke, ed. P.E Hovingh, 2000); VI, 6 (Annot. on John and Acts, ed. P.E Hovingh, 2003); VI, 8 (Annot. on 1-2 Corinthians, ed. M.L. van Poll-van de Lisdonk, 2003). The order of publication depends on when the respective volumes are finished. With regard to the edition of 'ordo' VI the Editorial Board is much indebted to Professor H.J. de Jonge (Leiden) for his expert advice. The Editorial Board and the editor of the present volume are grateful to all libraries that kindly put books, photostats, microfilms, and bibliographical material at their disposal.